Total Deformation and its Role in Heavy Precipitation Events Associated with Deformation-Dominant Flow Patterns - 高守亭 杨帅 薛明 崔春光 (Advances in atmospheric sciences, 2008)
In this paper, it is elucidated that the total deformation （TD）, defined as the square root of the sum of squared stretching deformation and squared shearing deformation, is an invariant independent of the coordinate system used. An idealized flow field is then constructed to demonstrate the confluence effect of a non-divergent and irrotational deformation field on moisture transport. To explore the characteristics and role of TD, one heavy rainfall case that occurred in the middle and lower reaches of the Yangtze River （MRYR） over China, associated with a front with shear line, is analyzed using the Weather Research and Forecasting （WRF） model output data. It is found that right before the occurrence of precipitation, the effect of the confluence induced by deformation on moisture transport provides a favorable condition for precipitation. During the precipitation, both location and orientation of the zone of large TD coincide with the confluent shear line. The rainhands are nearly parallel with, and located lightly to the south of the zones of large TD and the confluent shear line. The TD in the lower troposphere increases in value as precipitation persists. When TD approaches its maximal value, the next 6-hour precipitation reaches its peak correspondingly. A tendency equation for TD is derived. The analysis of linear correlation and RMS difference between individual terms in the total deformation equation and the sum of the terms shows that the pressure gradient plays a major role in determining the local change of total deformation.